2006
DOI: 10.1002/ajmg.a.31270
|View full text |Cite
|
Sign up to set email alerts
|

Blepharophimosis‐mental retardation (BMR) syndromes: A proposed clinical classification of the so‐called Ohdo syndrome, and delineation of two new BMR syndromes, one X‐linked and one autosomal recessive

Abstract: We report on 11 patients from 8 families with a blepharophimosis and mental retardation syndrome (BMRS) phenotype. Using current nosology, five sporadic patients have Ohdo syndrome, associated with congenital hypothyroidism in two of them (thus also compatible with a diagnosis of Young-Simpson syndrome). In two affected sibs with milder phenotype, compensated hypothyroidism was demonstrated. In another family, an affected boy was born to the unaffected sister of a previously reported patient. Finally, in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
3

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 33 publications
3
78
0
3
Order By: Relevance
“…Since 1987, nine more YSS patients have been published [Fryns and Moerman, 1988;Cavalcanti, 1989;Bonthron et al, 1993;Nakamura and Noma, 1997;Masuno et al, 1999;Kondoh et al, 2000;Verloes et al, 2006]. The manifestations in these patients are very similar to those seen in patients with a terminal deletion of the short arm of chromosome 1.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Since 1987, nine more YSS patients have been published [Fryns and Moerman, 1988;Cavalcanti, 1989;Bonthron et al, 1993;Nakamura and Noma, 1997;Masuno et al, 1999;Kondoh et al, 2000;Verloes et al, 2006]. The manifestations in these patients are very similar to those seen in patients with a terminal deletion of the short arm of chromosome 1.…”
Section: Introductionmentioning
confidence: 62%
“…This observation may partially explain why patients with 1p36 deletions have not been reported to have epicanthus inversus. Verloes et al [2006] suggested that YSS is probably genetically heterogeneous. We suggest, based on genetic testing along with clinical observation that YSS is due to a deletion in the terminal region on the short arm of chromosome 1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bu hastalarda flafl›-l›k ve ambliyopi s›kl›¤› normal nüfusa k›yasla daha yüksek saptanm›flt›r (2). Genifl ve düz burun kökü, damak ve kulak anomalileri, sporadik olarak mental retardasyon, gonadal anomaliler rastlanan göz d›fl› bulgulard›r (4)(5)(6).…”
Section: Giriflunclassified
“…[Ohdo et al, 1986]. In 2006, a new classification of BMRS delineating five groups was introduced in which the use of the term ''Ohdo syndrome'' was suggested to remain restricted to the original patients of Ohdo [Verloes et al, 2006]. Patients sharing a characteristic facial phenotype and a combination of additional anomalies including heart defects, optic atrophy, deafness, hypoplastic teeth, cleft palate, joint limitations, and hypothyroidism are referred to as having BMRS SBBYS type [Verloes et al, 2006].…”
Section: Introductionmentioning
confidence: 98%